A numerical and theoretical analysis of the structural performance for a new type of steel-concrete composite aqueduct. (15th October 2021) - Xiao, Jing-Lin; Yang, Yue; Zhuang, Liang-Dong; Nie, Xin
Highlights: A new type of steel-concrete composite aqueduct is proposed. Advantages of composite aqueduct compared with other aqueducts are demonstrated. Finite element model is established to study the properties of composite aqueduct. Parametric analyses are carried out in the longitudinal and transverse directions. A fiber model with shear lag is presented to facilitate the stress estimation. Abstract: A new type of steel-concrete composite aqueduct, made of steel trough and concrete cover connected by shear studs, is proposed. The composite aqueduct has better fluid tightness, lighter weight, higher capacity and faster construction speed compared with traditional prestressed concrete aqueducts; therefore, it has a broad potential to be applied in water transfer projects. To study the structural performance of the composite aqueduct, a fine finite element model is established by using ABAQUS, whose results are representative of the typical spatial deformations experienced by the aqueduct. Parametric analyses are carried out in the longitudinal and transverse directions. The results indicate that the longitudinal stress is higher than the transverse stress, and a significant shear lag is found on the steel bottom plate. Thus, design parameters are dictated by the longitudinal stress of the steel bottom plate. In order to facilitate the estimation of the longitudinal stress, a fiber model that considers the shear lag effect is developed. The formula of the effective width is fitted based on the results of a series of finite element-based parametric analyses. The fitted formula is more accurate and simpler compared to several national codes, and the error of the stress is usually less than 10%.